2018
DOI: 10.1634/theoncologist.2017-0384
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune-Related Adverse Events with Clinical Benefit in Patients with Advanced Non-Small-Cell Lung Cancer Treated with Nivolumab

Abstract: Immune-related adverse events (irAEs) are frequently observed with nivolumab monotherapy. This study evaluted whether the development of irAEs correlates with treatment response in advanced non-small-cell lung cancer. Results showed that the objective response rate and progression-free survival were significantly better in the patients who developed irAEs than in the patients who did not develop irAEs, and the incidence of irAEs and positivity for antithyroid antibody at pretreatment were independent predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
159
5
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(216 citation statements)
references
References 34 publications
28
159
5
6
Order By: Relevance
“…On the other hand, the differences in survival rates between the subgroups seem to us so impressive that with a bigger sample size, statistically significant differences would emerge. Interestingly, our finding of a higher incidence of irAEs of any grade in patients with non‐low SMM is consistent with recent reports that described significant associations between irAEs and a greater benefit with anti‐PD‐1/PD‐L1 treatments …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the differences in survival rates between the subgroups seem to us so impressive that with a bigger sample size, statistically significant differences would emerge. Interestingly, our finding of a higher incidence of irAEs of any grade in patients with non‐low SMM is consistent with recent reports that described significant associations between irAEs and a greater benefit with anti‐PD‐1/PD‐L1 treatments …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our finding of a higher incidence of irAEs of any grade in patients with non-low SMM is consistent with recent reports that described significant associations between irAEs and a greater benefit with anti-PD-1/PD-L1 treatments. 8,9 We cannot make any definitive conclusions, but only some speculative reflections on how nutritional status and body composition could affect the immune response and clinical outcomes of ICI treatments. Some authors have already speculated about the negative influence that alterations in body composition of sarcopenic patients could have on declining immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Immune‐related adverse events were not associated with better OS in patients with metastatic NSCLC. In concordance with our findings, several retrospective analyses have reported improved PFS and OS in patients with advanced NSCLC or melanoma that developed grade 2 or higher irAEs . A prospective cohort of 43 patients with NSCLC treated with nivolumab demonstrated a higher objective response rate in the patients that experienced irAEs (37%) compared with those without irAEs (17%), as well as longer median PFS (6.4 vs. 1.5 months) .…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several studies have reported a positive correlation between irAEs and improved clinical outcomes . However, an association between ILD and the efficacy of ICIs has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Recently, several studies have reported a positive correlation between irAEs and improved clinical outcomes. 6,7 However, an association between ILD and the efficacy of ICIs has not been fully investigated. The aim of this study was to evaluate the relationship between the development of ILD and clinical efficacy and to clarify the features and risk factors of ILD for patients with advanced NSCLC treated with ICIs.…”
Section: Introductionmentioning
confidence: 99%